The deathless one - Hamm, Emma (Gravesinger Series, 2025)
"Jessamine was raised to be a leader for her people, but when the land is overrun by an incurable plague, she must enter a political marriage to save them all. A union that should have brought hope only brings death as her new husband murders her at the wedding altar and seizes the throne. But her death is just the beginning. Her spirit is met by the Deathless One, a god of death yearning to return to the mortal plane, and he needs her help. The two of them make a deal -- her life and the return of her kingdom in exchange for his resurrection. But the Deathless One is a known trickster, and a deal with him is one made in blood. Jessamine knows the Deathless One is a dangerous ally, but the longer they work together, the more she wants him and the less she can stay away. As their connection deepens, soonshe wonders if she even wants this contract to end. Perhaps the more appealing throne is the one by his side, but she'd have to turn her back on her people to get it."--